Cell factory‐derived bioactive molecules with polymeric cryogel scaffold enhance the repair of subchondral cartilage defect in rabbits. (14th July 2015) - Gupta, Ankur; Bhat, Sumrita; Chaudhari, Bhushan P.; Gupta, Kailash C.; Tägil, Magnus; Zheng, Ming Hao; Kumar, Ashok; Lidgren, Lars
Abstract: We have explored the potential of cell factory‐derived bioactive molecules, isolated from conditioned media of primary goat chondrocytes, for the repair of subchondral cartilage defects. Enzyme‐linked immunosorbent assay (ELISA) confirms the presence of transforming growth factor‐ β 1 in an isolated protein fraction (12.56 ± 1.15 ng/mg protein fraction). These bioactive molecules were used alone or with chitosan–agarose–gelatin cryogel scaffolds, with and without chondrocytes, to check whether combined approaches further enhance cartilage repair. To evaluate this, an in vivo study was conducted on New Zealand rabbits in which a subchondral defect (4.5 mm wide × 4.5 mm deep) was surgically created. Starting after the operation, bioactive molecules were injected at the defect site at regular intervals of 14 days. Histopathological analysis showed that rabbits treated with bioactive molecules alone had cartilage regeneration after 4 weeks. However, rabbits treated with bioactive molecules along with scaffolds, with or without cells, showed cartilage formation after 3 weeks; 6 weeks after surgery, the cartilage regenerated in rabbits treated with either bioactive molecules alone or in combinations showed morphological similarities to native cartilage. No systemic cytotoxicity or inflammatory response was induced by any of the treatments. Further, ELISA was done to determine systemic toxicity, which showed no difference in concentration of tumour necrosis factor‐ α in blood serum, before or after surgery. In conclusion, intra‐articular injection with bioactive molecules alone may be used for the repair of subchondral cartilage defects, and bioactive molecules along with chondrocyte‐seeded scaffolds further enhance the repair. Copyright © 2015 John Wiley & Sons, Ltd.